The Copper(II)-Catalyzed Oxidation of Glutathione. - Ngamchuea, K; Batchelor-McAuley, C; Compton, R (Wiley, 2016)
The kinetics and mechanisms of the copper(II)-catalyzed GSH (glutathione) oxidation are examined in the light of its biological importance and in the use of blood and/or saliva samples for GSH monitoring. The rates of the free thiol consumption were measured spectrophotometrically by reaction with DTNB (5,5'-dithiobis-(2-nitrobenzoic acid)), showing that GSH is not auto-oxidized by oxygen in the absence of a catalyst. In the presence of Cu(2+) , reactions with two timescales were observed. The first step (short timescale) involves the fast formation of a copper-glutathione complex by the cysteine thiol. The second step (longer timescale) is the overall oxidation of GSH to GSSG (glutathione disulfide) catalyzed by copper(II). When the initial concentrations of GSH are at least threefold in excess of Cu(2+) , the rate law is deduced to be -d[thiol]/dt=k[copper-glutathione complex][O2 ](0.5) [H2 O2 ](-0.5) . The 0.5(th) reaction order with respect to O2 reveals a pre-equilibrium prior to the rate-determining step of the GSSG formation. In contrast to [Cu(2+) ] and [O2 ], the rate of the reactions decreases with increasing concentrations of GSH. This inverse relationship is proposed to be a result of the competing formation of an inactive form of the copper-glutathione complex (binding to glutamic and/or glycine moieties).